Deep Brain Stimulation in Parkinson’S Disease [Estimulación Cerebral Profunda en Enfermedad de Parkinson] - Chana-Cuevas, P; Kunstmann-Rioseco, C (Sociedad Medica de Santiago, 2018)
Background: Deep brain stimulation is an essential therapeutic tool in Parkinson ´s disease. Aim: To assess the results of a series of patients with Parkinson’s disease treated with micro-electrode guided subthalamic nucleus stimulation. Material and Methods: Twenty patients with idiopathic Parkinson’s disease were studied (10 males). Three months after surgery, we analyzed the change in motor disturbances, medication need to control symptoms and quality of life. Results: We observed a significant improvement in all the assessed variables. Motor involvement determined as OFF hours and expressed as percentage of the day changed from 30 ± 15 to 10 ± 7% in the preoperative and postoperative periods, respectively. ON hours without dyskinesia changed from 17 ± 16 to 78 ± 21%. ON hours with dyskinesia changed from 53 ± 23 to 12 ± 15%. Medication need changed from 1,505 ± 499 to 1,214 ± 528 levodopa equivalents. Parkinson’s Disease Questionnaire 39 score changed from 62.9 ± 22.7 to 34.3 ± 18.5. During the 5-year follow-up a continuous improvement of symptoms was observed. Conclusions: Micro-electrode guided subthalamic nucleus functional surgery in patients with Parkinson’s disease has good immediate and late results. © 2018, Sociedad Medica de Santiago. All rights reserved.